The Histone Demethylase JMJD1C Regulates CAMKK2-AMPK Signaling to Participate in Cardiac Hypertrophy - Yu, Shuang; Li, Yihong; Zhao, Hongwei; Wang, Qingdong; Chen, Ping (Frontiers in Physiology, 2020)
The roles of the histone demethylase JMJD1C in cardiac hypertrophy remain unknown. JMJD1C was overexpressed in hypertrophic hearts of humans and mice, whereas the histone methylation was reduced. Jmjd1c knockdown repressed the angiotensin II (Ang II)-mediated increase in cardiomyocyte size and overexpression of hypertrophic genes in cardiomyocytes. By contrast, JMJD1C overexpression promoted the hypertrophic response of cardiomyocytes. Our further molecular mechanism study revealed that JMJD1C regulated AMP-dependent kinase (AMPK) in cardiomyocytes. JMJD1C did not influence LKB1 but repressed Camkk2 expression in cardiomyocytes. Inhibition of CAMKK2 with STO609 blocked the effects of JMJD1C on AMPK. AMPK knockdown blocked the inhibitory functions of JMJD1C knockdown on Ang II-induced hypertrophic response, whereas metformin reduced the functions of JMJD1C and repressed the hypertrophic response in cardiomyocytes.